Pengaruh Visual Konten Influencer Terhadap Minat Beli Ulang Melalui Keputusan Pembelian - Cindi Norawati Sirait; Meitiana Meitiana; Vivy Kristinae; Aprilita Aprilita (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the influence of influencer visual content on repurchase intention mediated by purchase decisions. A quantitative method was used, with data collected through online questionnaires and analyzed using SmartPLS 4.0. The results indicate that influencer visual content has a significant effect on repurchase intention through purchase decisions. This conclusion highlights the importance of visual content in influencing purchase decisions and increasing followers’ repurchase intention.